The yeast F1-ATPase beta subunit precursor contains functionally redundant mitochondrial protein import information. - Bedwell, D M (1987)
The NH2 terminus of the yeast F1-ATPase beta subunit precursor directs the import of this protein into mitochondria. To define the functionally important components of this import signal, oligonucleotide-directed mutagenesis was used to introduce a series of deletion and missense mutations into the gene encoding the F1-beta subunit precursor. Among these mutations were three nonoverlapping deletions, two within the 19-amino-acid presequence (delta 5-12 and delta 16-19) and one within the mature protein (delta 28-34). Characterization of the mitochondrial import properties of various mutant F1-beta subunit proteins containing different combinations of these deletions showed that import was blocked only when all three deletions were combined. Mutant proteins containing all possible single and pairwise combinations of these deletions were found to retain the ability to direct mitochondrial import of the F1-beta subunit. These data suggest that the F1-beta subunit contains redundant import information at its NH2 terminus. In fact, we found that deletion of the entire F1-beta subunit presequence did not prevent import, indicating that a functional mitochondrial import signal is present near the NH2 terminus of the mature protein. Furthermore, by analyzing mitochondrial import of the various mutant proteins in [rho-] yeast, we obtained evidence that different segments of the F1-beta subunit import signal may act in an additive or cooperative manner to optimize the import properties of this protein.